Chemically-doped graphene with improved surface plasmon characteristics: an optical near-field study. Issue 37 (9th August 2016) - Zheng, Zebo; Wang, Weiliang; Ma, Teng; Deng, Zexiang; Ke, Yanlin; Zhan, Runze; Zou, Qionghui; Ren, Wencai; Chen, Jun; She, Juncong; Zhang, Yu; Liu, Fei; et al.
Abstract : The surface plasmon characteristics of chemically-doped graphene were systematically studied using the scanning near-field optical technique. Abstract : One of the most fascinating and important merits of graphene plasmonics is their tunability over a wide range. While chemical doping has proven to be a facile and effective way to create graphene plasmons, most of the previous studies focused on the macroscopic behaviors of the plasmons in chemically-doped graphene and little was known about their nanoscale responses and related mechanisms. Here, to the best of our knowledge, we present the first experimental near-field optical study on chemically-doped graphene with improved surface plasmon characteristics. By using a scattering-type scanning near-field optical microscope (s-SNOM), we managed to show that the graphene plasmons can be tuned and improved using a facile chemical doping method. Specifically, the plasmon interference patterns near the edge of the monolayer graphene were substantially enhanced via nitric acid (HNO3 ) exposure. The plasmon-related characteristics can be deduced by analyzing such plasmonic fringes, which exhibited a longer plasmon wavelength and reduced plasmon damping rate. In addition, the local carrier density and therefore the Fermi energy level ( E F ) of graphene can be obtained from the plasmonic nano-imaging, which indicated that the enhanced plasmon oscillation originated from the injection of free holes into graphene by HNO3 . These findings were further corroborated by theoretical calculations using density functional theory (DFT). We believe that our findings provide a clear nanoscale picture on improving graphene plasmonics by chemical doping, which will be helpful for optimizing graphene plasmonics and for elucidating the mechanisms of two-dimensional light confinement by atomically thick materials.